2009
DOI: 10.1021/bc900281b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Clicked Curcumin and Clicked KLVFFA Conjugates as Inhibitors of β-Amyloid Fibril Formation

Abstract: Abnormal aggregation of beta-amyloid (Abeta) peptides into toxic aggregates has been identified as a key event in Alzheimer's disease (AD). Inhibition of this process has thus emerged as a major therapeutic track against AD. The present work describes the synthesis and in vitro study of a novel class of inhibitors. Two copies of Abeta-binding motifs (either curcumin or the KLVFFA peptide) are clicked via copper(I)-mediated azide-alkyne cycloaddition on a constrained cyclopeptide scaffold designed to interfere … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 60 publications
0
71
0
Order By: Relevance
“…Earlier we have also shown that the curcumin rescues the protein from aggregation by increasing the reconfiguration rate [15]. Moreover, many researchers using a diverse group of peptides and proteins have demonstrated that curcumin inhibits fibril formation through one or other mechanisms [11,[14][15][16][17][18][19][20]. These studies form a very strong basis for the inhibitor hypothesis of curcumin.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Earlier we have also shown that the curcumin rescues the protein from aggregation by increasing the reconfiguration rate [15]. Moreover, many researchers using a diverse group of peptides and proteins have demonstrated that curcumin inhibits fibril formation through one or other mechanisms [11,[14][15][16][17][18][19][20]. These studies form a very strong basis for the inhibitor hypothesis of curcumin.…”
Section: Introductionmentioning
confidence: 77%
“…These results indicated that F isomers preincubated with curcumin acquired a state which is more susceptible to aggregation than the N isomer. Curcumin, the main polyphenolic compound found in the spice turmeric, has been shown to inhibit fibrillar aggregation of different types of protein and peptides [14][15][16][17][18][19][20]. Recently, two independent works on the effect of curcumin on the amyloid fibril formation showed that curcumin promoted amyloid fibril formation by binding to oligomeric species of intrinsically disordered proteins (IDPs) [21,22].…”
Section: Effect Of Curcumin On the Unfolding And Stability Of Hsa Isomentioning
confidence: 99%
“…Their therapeutic use is limited by their poor targeting and low permeability to the bloodbrain barrier (BBB) and/or toxic effects. [ 8 ] To overcome these limitations, novel molecules and materials designed to inhibit A β aggregation and disaggregate A β fi brils are urgently needed. It is known that amyloid formation is highly dependent upon multiple factors such as pH, temperature, protein concentration, and ionic strength.…”
Section: Doi: 101002/adma201104864mentioning
confidence: 99%
“…[ 181 ] However, the therapeutic use of AD agents at present is limited by their poor targeting and low permeability to the bloodbrain barrier (BBB) and/or toxic effects. [ 182 ] So exploring local heat generation (hyperthermia) can act as an effective means to dissolve amyloid deposits of A β . Irradiation in the NIR window can penetrate tissues with suffi cient intensity and higher spatial precision for inducing localized hyperthermia, while avoiding nonspecifi c heating of surrounding tissues.…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%